Nilai Kebersamaan dalam Keluarga - Ira Kusumawaty; Yunike Yunike; Miskiyah Miskiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore parents' perceptions of the importance of togetherness in the family and to examine the types of physical activities carried out by the family, including frequency, nature, and constraints. Methods Semi-structured telephone interviews were conducted with 35 parents of children aged 10 to 12 who attended schools in low, middle, and high socioeconomic status environments. Interviews were transcribed using verbatim, anonymized, and analyzed. The results showed that most parents valued family involvement in physical activity as necessary. The benefits of joint activities can increase parent-child interaction and communication, take advantage of the time together, improve mental health and physical fitness, and control weight. However, it was found that families rarely did physical activities together as a family unit, and any activities done together were usually sedentary. Schedule complexity hinders the implementation of activities with the family, in addition to busy lifestyles, differences in ages and interests of children and adults, lousy weather, and lack of access to facilities, transportation, and activity costs. In conclusion, family-based interventions must be prioritized for implementation in accommodating complex family demands and needs by taking into account the affordability and capabilities of the family. Keywords: Physical Activity, Family Interaction, Togetherness Values, Mental Health.